Effects of 28-day Rotation of Monensin and Laidlomycin Propionate on Commercial Cattle Performance During the Growing Phase - Madison L. Bemisderfer (Kansas Agricultural Experiment Station Research Reports, 2026)
Objective: Investigate the effects of multiple 28-day rotations of monensin (Rumensin 90; Elanco, Indianapolis, IN) and laidlomycin propionate (Cattlyst 50G; Phibro Animal Health Corporation, Teaneck, NJ) on growing commercial heifer performance. Study Description: A total of 584 heifers (639 ± 57 lb initial body weight [BW]) were randomly divided among 10 pens at a commercial feedyard. All heifers were limit-fed a growing ration with treatment assigned as: 1) monensin (MON) included at 18.8 g/ton on a dry matter (DM) basis; or 2) 28-day rotation (ROT) of monensin (included at 18.8 g/ton on a DM basis) to laidlomycin propionate (included at 7.4 g/ ton on a DM basis) repeated twice during the 112-day trial. Performance was assessed with BW measurements every 28 days. The Bottom Line: Rotating monensin and laidlomycin propionate every 28 days during the growing phase improved the performance of limit-fed beef heifers by 8.7% compared to consistent monensin feeding, indicating a label-compliant strategy with possible performance value.
Keywords: ionophores; growing heifers; performance